Hospitality - a paradigm of interreligious and intercultural encounter = Gastfreundschaft als Paradigma interreligiöser und interkultureller Begegnung - Reiterer, Friedrich V. 1947-; Udeani, Chibueze C.; Zapotoczky, Klaus, 1938- (Intercultural Theology and Study of Religions, 2012)
The global community is currently being confronted with an increasing urgent demand for dialogue among cultures and religions. The question arises with regards to efficient concepts or tools which will help to shape the encounter of the different religions and cultures of the world with one another. Indicative here is the cognition that hospitality has to do with a factor which is proven in almost all religions and cultures of the world. Hospitality is primarily an existential encounter and as such it brings also the experience of difference in socio-religious traditions and in intercultural relations. Gegenwärtig wird in der Weltöffentlichkeit mit zunehmender Dringlichkeit die Forderung nach einem Dialog der Kulturen und der Religionen erhoben. Vor diesem Hintergrund stellt sich die Frage nach tragfähigen Konzepten, welche die Begegnung der Religionen und Kulturen der Welt gestalten helfen. Wegweisend hierfür ist die Erkenntnis, dass es sich bei der Gastfreundschaft um eine Gegebenheit handelt, welche in nahezu allen Religionen und Kulturen der Welt belegt ist. Gastfreundschaft ist zuallererst existentielle Begegnung und bringt als solche auch die Erfahrung der Differenz in die sozio-religiösen Traditionen und in die interkulturellen Beziehungen.